The Intelligence Function of the Bandung City National Narcotics Agency in Preventing Drug Circulation - Bj, Abdul Muis (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The abuse and illicit trafficking of narcotics has been increasing in Indonesia both in quality and quantity. Not only the general public, but also many law enforcement officials have been proven to be perpetrators of narcotics crimes. Especially when TNI soldiers who maintain the integrity and sovereignty of the territory of the Unitary State of the Republic of Indonesia are involved in narcotics offences. The government established the National Narcotics Agency to eradicate narcotics crimes, which is authorised to investigate and prosecute narcotics crimes in Indonesia. In the procedural law, it has been stated that investigators and investigators of a narcotics crime within the TNI are ANKUM, Military Police, Oditur and auxiliary investigators. The authority of BNN in conducting investigations and investigations of narcotics offences against TNI soldiers in cases of connexity is also very limited. The investigation and investigation must be authorised by ANKUM and only for case development to obtain information and data to find other suspects who are civilians. Once the information required by BNN is deemed sufficient, BNN must still refer the case to ANKUM and the Military Police as operational investigators and core investigators in koneksitas cases for TNI soldiers.